The centennial of the Philippine Independence a Bangsamoro perspective - Kamlian, Jamail A. (1999)
At present the entire nation is commemorating the Centennial of the Philippine Revolution against Spain, which gave birth to the First Philippine Republic in Malolos, Bulacan, on January 23, 1899, the first in Asia. As I understand, there are two important reasons for this commemoration: 1) to recall with great pride and honor our victory after our long and difficult struggles against Spanish colonial aggressors, and 2) to give due recognition to our revolutionary leaders and heroes and express our deep appreciation of their noble deeds. However, it has been observed that many among the Lumads and the Bangsamoro peoples of Mindanao and Sulu are somewhat indifferent to this issue. They simply cannot identify with our commemorative activities because they believe that they did not have any part in the revolution. They actually had their own successful struggles against the same enemy. Unfortunately, such acts of heroism have been taken for granted and not given due recognition in the official documents of the government thereby creating an air of official indifference which in turn leads to similar acts of omission in academic circles. This paper is divided into two parts. The first part presents an analysis of the historical basis for the Bangsamoro's attitude of indifference towards the celebration of the Centennial of the Republic of the Philippines. The second part cites some basic considerations in the advocacy for nation unity and nationhood.
Keywords: Muslims -- Philippines -- Attitudes; Philippines -- History -- 1898-.; Philippines -- Centennial celebrations, etc